2014
DOI: 10.1159/000361054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the <b><i>FTO</i></b> rs9930506 Polymorphism on the Main Comorbidities of the Cardiorenal Metabolic Syndrome in an Elderly Spanish Cohort

Abstract: Background/Aim: Fat mass and obesity-associated (FTO) gene polymorphisms have been linked to the risk of obesity and diabetes, two well-recognized risk factors for renal disease. Our aim was to determine whether a common FTO polymorphism was associated with a reduced estimated glomerular filtration rate (eGFR) independently of body mass index (BMI) and type 2 diabetes mellitus (T2DM) in a cohort of elderly individuals from the region of Asturias (Northern Spain; RENASTUR cohort). Methods: A total of 544 Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Consistent with the literature, we found that the eGFR value was higher in patients with MetS, but there was no significant difference between genotypes/alleles frequencies of the FTO gene. Coto et al did not find any relationship between FTO gene rs9930506 polymorphism and reduced eGFR in the elderly patients with MetS [14]. It has been reported a significant association between FTO gene (rs17817449, rs708259 polymorphisms) and chronic kidney disease [12,13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with the literature, we found that the eGFR value was higher in patients with MetS, but there was no significant difference between genotypes/alleles frequencies of the FTO gene. Coto et al did not find any relationship between FTO gene rs9930506 polymorphism and reduced eGFR in the elderly patients with MetS [14]. It has been reported a significant association between FTO gene (rs17817449, rs708259 polymorphisms) and chronic kidney disease [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…Increased estimated glomerular filtration rate (eGFR) (glomerular hyperfiltration) is one of the early signs of renal complications [10,11]. Based on our current information, there are limited data about the association of rs9939609 variant in FTO gene and hyperfiltration in obese adolescents [12][13][14].…”
mentioning
confidence: 99%
“…In addition, both SNPs were correlated with the early onset of childhood obesity [ 15 ]. In another study by Coto et al carried out among an elderly Caucasian–Spanish population, the frequency of the GG genotype of the rs9930506 polymorphism in people with a BMI higher than 25 was significantly higher than other subjects [ 22 ]. However, some studies have reported contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…All them were Caucasian, aged 56-85 years (45 % male), and from the region of Asturias (Northern Spain, total population one million), and were recruited through the Primary Health Care Center of the city of Oviedo to evaluate the renal function in healthy elderly people [16,17]. Individuals with a history of chronic renal disease or who had suffered cardiovascular disease episodes were not eligible for the study.…”
Section: Study Subjectsmentioning
confidence: 99%